Skype™ conference calls: a way to promote speaking skills in the teaching and learning of english (2015)
This article presents the results of a research project on the teaching and learning of English through the use of Skype™ conference calls. The research was carried out with a group of 12 English as a foreign language adult learners in the language institute of Universidad Distrital Francisco José de Caldas, Bogotá, Colombia. The findings of this study suggest that Skype™ conference calls might be considered as an influential computer-mediated communication tool in order to promote English as a foreign language adult A1 learners’ speaking skill, especially for social interaction purposes and oral reinforcement of both language fluency and course contents outside of classroom settings.Este artículo presenta los resultados de una investigación sobre la enseñanza y el aprendizaje de inglés a través de llamadas para conferencia en Skype™. Esta investigación se realizó con un grupo de 12 estudiantes adultos de inglés como lengua extranjera en el instituto de lenguas de la Universidad Distrital en Bogotá, Colombia. Los resultados de este estudio muestran que las llamadas para conferencia en Skype™ pueden influir positivamente a la hora de promover la habilidad de habla de estudiantes adultos de inglés como lengua extranjera, especialmente con fines de interacción social y refuerzo oral tanto de los contenidos de clase como la fluidez en el lenguaje fuera del aula de clase.